Cost-effectiveness analysis of imidapril (Vascor) compared to metoprolol (Neobloc) in the treatment of Stage 1 essential hypertension among Filipino patients seen at the Philippine General Hospital - He Wentian
Background The treatment of hypetension involves a long-term course which results in great economic and social costs. The high prevalence of hypertension in the Philippines mandates pharmacoeconomic evaluation of antihypertensive drugs in order to promote rational drug selection. Objective To evaluate the cost-effectiveness of imidapril and metoprolol as monotherapy in Filipino patients with Stage 1 essential hypertension. Study design Cost-effectiveness analysis from the perspective of the health care payer. Method Retrospective cross-sectional analysis was done based on the review of hospital records of out-patients aged 40-70 years old, with Stage 1 essential hypertension and follow-up treatment of 3 months at the Philippine General Hospital (PGH). Evaluation of effectiveness was based on 2 parameters: 1) percentage of patients achieving target blood pressure
TM superscript after Vascor and Neobloc on title.
Thesis (MS in Pharmacology)--University of the Philippines Manila.
Keywords: Hypertension; Drugs